Sequential multiple mediating effect of loneliness and family health on physical frailty and willingness to age at home in older adults: a national survey in China - Xuan Wang; Yifan Jiang; Zhiyong Xu; Lin Qi; Yibo Wu; Min Zhang (BMC Geriatrics)
Abstract Background With the rapid ageing of the global population, the number of older adults with physical frailty has been gradually increasing, making ageing at home a key strategy for coping with this demographic change. The opinions of older adults regarding their willingness to age at home deserve to be considered respectfully. As a result, this study aimed to investigate willingness to age at home and any associated underlying mechanisms involving physical frailty among older Chinese adults. Methods This study was a national cross-sectional survey. Stratified random and quota sampling were used before and after the individual level respectively. Willingness to age at home was compared between older adults with different characteristics using the Mann–Whitney U test and Kruskal–Wallis H test. A Spearman rank test was conducted to explore the correlations among physical frailty, loneliness, family health, and willingness to age at home. The path hypothesis that loneliness and family health influence the relationship between physical frailty and willingness to age at home among older adults was further tested through sequential multiple mediation analysis. Results A total of 3,837 older adults were included in this study. They returned a median score of 78 in terms of willingness to age at home. Physical frailty (β = − 0.044, P < 0.01) and loneliness (β = − 0.070, P < 0.001) were negatively associated, and family health (β = 0.275, P < 0.001) was positively associated with a willingness to age at home among older Chinese adults. Loneliness and family health played sequential multiple mediating role (β = − 0.018, Boot SE = 0.002, 95% CI = [–0.022, − 0.014]) between physical frailty and willingness to age at home. Conclusions Reducing physical frailty in older adults, reducing their sense of loneliness, and enhancing their family health is essential, as it can increase their levels of confidence with regard to ageing at home.